Atomic and molecular LIBS spectra of Al alloys and composite materials for nanosecond and microsecond excitation - Ostrowski, Roman; Skrzeczanowski, Wojciech; Rycyk, Antoni; Czyż, Krzysztof; Sarzyński, Antoni; Strzelec, Marek; Jach, Karol; Świerczyński, Robert (Photonics Letters of Poland, 2017)
Spectral investigations in the UV-VIS range of selected Al alloys and composites, used in the construction of armament components as well as drones, were performed using LIBS technique. Two Nd:YAG lasers were applied: a short pulse 4 ns 60 mJ laser and a long pulse 200/400 (up to 1000) us ( 2/4 up to 10 J) laser. In experiments with a short laser pulse only atomic spectra were observed while for long pulses, also molecular transitions have been recorded. Electron temperatures of created plasma were found on the base of Boltzmann law. Temperatures are clearly higher for short pulse excitation. Full Text: PDF References A. Miziolek, V. Palleschi and I. Schechter, Laser-Induced Breakdown Spectroscopy (Cambridge, Cambridge University Press 2006). CrossRef M. Sabsabi and P. Cielo, "Quantitative Analysis of Aluminum Alloys by Laser-Induced Breakdown Spectroscopy and Plasma Characterization", Appl. Spectrosc. 49, 499 (1995). CrossRef D.L. Death, A.P. Cunningham, and L.J. Pollard, "Multi-element analysis of iron ore pellets by Laser-induced Breakdown Spectroscopy and Principal Components Regression", Spectrochim. Acta B, 63, 763 (2008). CrossRef S. Laville, M. Sabsabi and F. Doucet, "Multi-elemental analysis of solidified mineral melt samples by Laser-Induced Breakdown Spectroscopy coupled with a linear multivariate calibration", Spectrochim. Acta B, 62, 1557 (2007), CrossRef D.M. Surmick, C.G, Parigger, "Aluminum Monoxide Emission Measurements in a Laser-Induced Plasma", Applied Spectroscopy, 2015, V.68, No.9, P.992-996. CrossRef J.B. Sirven, B. Bousquet, L. Canioni and L. Sarger,"Laser-Induced Breakdown Spectroscopy of Composite Samples: Comparison of Advanced Chemometrics Methods", Anal. Chem. 78, 1462 (2006). CrossRef E.J. Judge, G. Heck, E.B. Cerkez and R. J. Levis, "Discrimination of Composite Graphite Samples Using Remote Filament-Induced Breakdown Spectroscopy", Anal. Chem. 81, 2658 (2009). CrossRef L.M. Cabalin and J.J. Laserna, "Experimental determination of laser induced breakdown thresholds of metals under nanosecond Q-switched laser operation", Spectrochim. Acta B, 53, 723 (1998). CrossRef T.A. Labutin, A.M. Popov, V.N. Lednev and N.B. Zorov, "Correlation between properties of a solid sample and laser-induced plasma parameters", Spectrochim. Acta B, 64, 938 (2009). CrossRef J.S. Cowpe, R.D. Moorehead, D. Moser, J.S. Astin, and S. Karthikeyan, "Hardness determination of bio-ceramics using Laser-Induced Breakdown Spectroscopy", Spectrochim. Acta B, 66, 290 (2011). CrossRef G. Cristoforetti, , S. Legnaioli, V. Palleschi, A. Salvetti, and E. Tognoni, "Effect of target composition on the emission enhancement observed in Double-Pulse Laser-Induced Breakdown Spectroscopy", Spectrochim. Acta B, 63, 312 (2008). CrossRef